Pink salmon fishery in the Far-Eastern fishing basin in 2023: preliminary studies, forecast, interpretation of the fishing season results - E. A. Shevlyakov; A. A. Somov; V. A. Shevlyakov; A. N. Kanzeparova; N. A. Dederer; I. V. Melnikov (Известия ТИНРО, 2024)
Data of the trawl surveys for counting of pink salmon in 2022 and 2023 and results of pink salmon fishery in the main areas of the Russian Far East in 2023 are presented and the studies for understanding the state of the main pink salmon stocks and regional complexes are overviewed. The total catch in the Far-Eastern fishing basin was 478.5.103 t in 2023, including 182.4.103 t in the Bering Sea (total run — 247.1.106 ind.) and 280.8.103 t in the Okhotsk Sea (total run — 292.4.106 ind.). These values slightly exceed the forecasts of pink salmon run and catch in the Bering and Okhotsk Seas (estimated catch rates 140–150.103 t and 240–255.103 t, runs 210.106 ind. and 260–270.106 ind., respectively). For the forecast for the Okhotsk Sea, materials on differentiation of mixed pink salmon assemblages were analyzed by specialists of the Kamchatka branch of VNIRO, using both traditional methods (as morphological express- method and genetic method based on mt-DNA analysis) and a new method based on SNP-locus variability.